Some parasitic helminths of the Belcher's gull (Larus belcheri) - Gomez-Puerta, Luis A. (2019)
Information on parasitic helminths of seabirds is very limited in Peru. In the present work, helminths collected from the Belcher's gull (Larus belcheri) from some beaches of Lima (Pucusana, Chorrillos, Ventanilla and Ancón) in Peru were identified. The helminths were studied morphologically and identified as Skrjabinoclava sp. (Nematoda), Contracaecum sp. (Nematoda), Maritrema sp. (Trematoda) and Profilicollis altmani (Acanthocephala). The present work corresponds to the first records of these parasites in the Peruvian gull.